1998
DOI: 10.1074/jbc.273.29.18567
|View full text |Cite
|
Sign up to set email alerts
|

Switching of Platelet-activating Factor Acetylhydrolase Catalytic Subunits in Developing Rat Brain

Abstract: In a previous study, we demonstrated that Plateletactivating Factor (PAF) acetylhydrolase purified from bovine brain cortical cytosol consists of two mutually homologous catalytic subunits (␣1 and ␣2) and one putative regulatory ␤ subunit. The latter is a product of the LIS1 gene, which is defective in the Miller-Dieker syndrome, a form of lissencephaly. In this study, we examined the expression patterns of these three subunits in the developing rat brain. All three subunits were expressed in embryonic brain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 29 publications
3
53
0
2
Order By: Relevance
“…PAF-AH I ␣ 2 /␣ 2 is known to hydrolyze PAF more efficiently than ␣ 1 /␣ 1 homodimers, and it is likely that reducing PAF-AH ␣ 1 coincident with PAF-AH ␣ 2 induction would promote more rapid formation of ␣ 2 /␣ 2 homodimers, enhance PAF hydrolysis, and increase cell survival. Most interestingly, this phenomenon models the graded reduction in ␣ 1 observed over the course of cerebral development by changing the predominant PAF-AH I catalytic composition from ␣ 1 /␣ 2 heterodimers in embryonic central nervous system to ␣ 2 /␣ 2 homodimers in adult brain (51). Our data suggest that this shift may render adult brain more resistant to PAF challenge than embryonic brain.…”
Section: Cytosolic Paf-ahs Can Be Targeted Pharmacologically To Promomentioning
confidence: 74%
“…PAF-AH I ␣ 2 /␣ 2 is known to hydrolyze PAF more efficiently than ␣ 1 /␣ 1 homodimers, and it is likely that reducing PAF-AH ␣ 1 coincident with PAF-AH ␣ 2 induction would promote more rapid formation of ␣ 2 /␣ 2 homodimers, enhance PAF hydrolysis, and increase cell survival. Most interestingly, this phenomenon models the graded reduction in ␣ 1 observed over the course of cerebral development by changing the predominant PAF-AH I catalytic composition from ␣ 1 /␣ 2 heterodimers in embryonic central nervous system to ␣ 2 /␣ 2 homodimers in adult brain (51). Our data suggest that this shift may render adult brain more resistant to PAF challenge than embryonic brain.…”
Section: Cytosolic Paf-ahs Can Be Targeted Pharmacologically To Promomentioning
confidence: 74%
“…46,47 A homolog for the catalytic subunit in Drosophila was identified. However, it lacks both enzymatic activity and the ability to interact with LIS1.…”
Section: Paf-ahmentioning
confidence: 99%
“…In the present study, we identified (with at least 3 peptides) 23 proteins with significantly increased (Table 1) and 23 proteins with decreased ( Table 2) (1) - (Chihara et al, 2007), (2) - (Folci et al, 2014), (3) - (Chen et al, 2002), (4) - (Tanaka et al, 2000), (5) - (Ding and Shen, 2008), (6) - (Na et al, 2012), (7) - (Lyon et al, 2007), (8) - (Sweatt et al, 2004), (9) - (Bahn et al, 2002), (10) - (Manya et al, 1998), (11) - (Kamada et al, 2003), (12) - (McKenna et al, 2000), (13) - (Christel et al, 2012), (GO) -According to Gene Ontology database. …”
Section: Functional Clusters Of Altered Proteinsmentioning
confidence: 99%